2017
DOI: 10.1016/j.medici.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A role of alpha-tocopherol and phylloquinone in the modulation of uterine contractility and reproductive function in mouse models

Abstract: Alpha-tocopherol and phylloquinone have been shown to directly modulate uterine contractility and reproductive function and may contribute to the management and treatment of reproductive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It would be interesting to find out whether these processes also occur in UFs. This has not been studied yet, but these results could be also explained by estrogen-like properties of vitamin E. Bafor et al, in a very interesting study about the effects of AT on the concentrations of reproductive hormones in mice, found that treatment with AT significantly increased the plasma levels of luteinizing hormone (LH), estradiol, and progesterone [ 70 ]. They also found that AT affected not only the hypophysis alone (effect on LH), but also the ovaries (effect on estrogen and progesterone) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to find out whether these processes also occur in UFs. This has not been studied yet, but these results could be also explained by estrogen-like properties of vitamin E. Bafor et al, in a very interesting study about the effects of AT on the concentrations of reproductive hormones in mice, found that treatment with AT significantly increased the plasma levels of luteinizing hormone (LH), estradiol, and progesterone [ 70 ]. They also found that AT affected not only the hypophysis alone (effect on LH), but also the ovaries (effect on estrogen and progesterone) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each concentration was allowed a contact time of 5 min. (Bafor et al, 2017a). This procedure was performed for both non-pregnant and pregnant mouse uteri.…”
Section: Experiments On Spontaneous Uterine Contractilitymentioning
confidence: 99%
“…A contact time of 3 min was allowed following each concentration of http://www.jomped.co.za Open Access extract administered. After each set of administration, the tissues were washed three times and a washout period minimum of 10 min was allowed for the tissue to recover before the next administration (Bafor et al 2017).…”
Section: Experiments On the Effect Of Extract On Spontaneous Uterine Contractionmentioning
confidence: 99%